An Update of the Grützbalgϕ Hypothesis: The Role of Thrombosis and Coagulation in Atherosclerotic Progression - Yee, Karen O.; Ikari, Yuji; Schwartz, Stephen M. (Thrombosis and Haemostasis, 2001)
While a great deal has been learned about the initiation of atherosclerosis, much less is known about the factors that ultimately determine progression and clinical manifestations. In this review we will focus on the possible role of coagulation, especially intramural fibrin in lesion progression.
Keywords: Atherosclerosis; plaque rupture; coagulation; remodelling